Simplify
1\√19-√360+
1\√21 -√ 440+
1\√20 + √396
![](https://hi-static.z-dn.net/files/d90/bd9975856503a0f3b96b0b0d41ef5ef2.jpg)
Answers
Step-by-step explanation:
Correction:-
1/√[19 - √(360)] - 1/√[21 - √(440)] + 2/√[20 + √(396)] = ?
To find:-
Simplify.
Solution:-
We have,
1/√[19 - √(360)] - 1/√[21 - √(440)] + 2/√[20 + √(396)]
= 1/√[19 - 2√(90)] - 1/√[21 - 2√(110)] + 2/√[20 + 2√(99)]
= 1/√[(√10)^2 + √(9)^2 - 2√(10)√(9)] - 1/√[(10)^2 + (√11)^2 - 2√(10)√(11)] + 2/√[(11)^2 + (√9)^2 - 2√(11)√(9)]
= 1/√[{√(10) - √(9)}]^2 - 1/√[{√(11) - √(10)}]^2 + 2/√[{√(11) + √(9)}]^2
= 1/[√(10) - √(9)] - 1/[√(11) - √(10)] + 2/[√(11) - √(9)]
= [1/{√(10) - √(9)} × {√(10) + √(9)}/{√(10) + √(9)] - [1/{√(11) - √(10)} × {√(11) + √(10)}/{√(11) + √(10)] + [2/{√(11) + √(9)} × {√(11) - √(9)}/{√(11) - √(9)}]
= [{√(10) + √(9)}/(10 - 9)] - [{√(11) + √(10)}/(11 - 10)] + [2{√(11) - √(9)}/(11 - 9)]
= [{√(10) + √(9)}/1] - [{√(11) + √(10)}/1] + [2{√(11) - √(9)}/2]
= √(10) + √(9) - √(11) - √(10) + [2{√(11) - √(9)}/2]
= √(10) + √(9) - √(11) - √(10) + √(11) - √(9)
= 0 Ans.
![](https://hi-static.z-dn.net/files/d1b/f3b1f549d2204b25b51b6039d56a51db.jpg)
![](https://hi-static.z-dn.net/files/ddc/6f0d9aaba333bc9cc725dcb3f3cf1b85.jpg)